2020
DOI: 10.1088/1742-6596/1465/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of metacognitive skills and creative thinking skills in STEM education at senior high school for biotechnology

Abstract: Biotechnology material will be more meaningful if done with practice. STEM education in improving student skills and is very suitable when collaborated with biotechnology materials. This study aims to analyze the metacognitive skills and creative thinking of students at STEM education in senior high school. The analysis in this paper uses descriptive analysis using mix method analysis. The sample in this study was 150 senior high school students. Data was collected using questionnaires and observations. Data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Through the problem of flood losses, students were given project assignments to make designs and miniatures of floating mosques. Giving projects can hone students' scientific creativity (Erdogan et al, 2013;Knezek et al, 2013;Gülhan & Şahin, 2016;Kustiana et al, 2020). Design activities are a means to develop creativity (Gibson, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Through the problem of flood losses, students were given project assignments to make designs and miniatures of floating mosques. Giving projects can hone students' scientific creativity (Erdogan et al, 2013;Knezek et al, 2013;Gülhan & Şahin, 2016;Kustiana et al, 2020). Design activities are a means to develop creativity (Gibson, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Through deeper learning, students develop expertise in a particular discipline or subject area. Kustiana et al, (2020) found that through cognitive, affective, and metacognitive mechanisms that students exposed to the non-successful-driven scaffolding showed a higher quality of constructive reasoning. In addition, the metacognitive and creative thinking skills of STEM education students in biotechnology were investigated using a mixed methods design (Kustiana et al, 2020).…”
Section: Metacognitionmentioning
confidence: 93%
“…It has also been found that Inclusive STEM High Schools (ISHSs) that speci cally enroll underrepresented students have blurred the boundaries of formal and informal education by melding traditional STEM instruction and providing opportunities for students to interact with local STEM communities, which inspired students to do STEM that mirrors that of professionals, augmented their STEM competencies, and provided them with the social capital to pursue STEM careers (Lynch et al, 2017). A large body of literature also points to the bene ts of informal learning experiences, especially for students from historically marginalized and underrepresented communities ( Kustiana et al, 2020). In the following section, we will outline the conceptual frameworks that guide our study.…”
Section: Introductionmentioning
confidence: 99%
“…Biotechnology is a branch of science that arose from scientific curiosity and is critical for students to comprehend because of its possible influence on them and others (Kustiana, Suratno, & Wahyuni, 2020). By providing a wide range of products, rapid developments in biotechnology and genetic engineering have shown their impact on our lives directly or indirectly in many areas, such as health, agriculture, the environment, and food production (Ayar & Hasipek, 2003;Lyson, 2002;Özgen, 1995).…”
Section: Introductionmentioning
confidence: 99%